Better evidence: prospective cohort study assessing the utility of an evidence-based clinical resource at the University of Rwanda. Issue 8 (7th August 2019) - Valtis, Yannis K; Rosenberg, Julie D; Wachter, Keri; Kisenge, Rodrick; Mashili, Fredirick; Chande Mallya, Rehema; Walker, Timothy David; Kabakambira, J Damascene; Egide, Abahuje; Ntacyabukura, Blaise; Weintraub, Rebecca
Abstract : Objective: Evidence-based clinical resources (EBCRs) have the potential to improve diagnostic and therapeutic accuracy. The majority of US teaching medical institutions have incorporated them into clinical training. Many EBCRs are subscription based, and their cost is prohibitive for most clinicians and trainees in low-income and middle-income countries. We sought to determine the utility of EBCRs in an East African medical school. Setting: The University of Rwanda (UR), a medical school located in East Africa. Participants: Medical students and faculty members at UR. Interventions: We offered medical students and faculty at UR free access to UpToDate, a leading EBCR and conducted a cohort study to assess its uptake and usage. Students completed two surveys on their study habits and gave us permission to access their activity on UpToDate and their grades. Results: Of the 980 medical students invited to enrol over 2 years, 547 did (56%). Of eligible final year students, 88% enrolled. At baseline, 92% of students reported ownership of an internet-capable device, and the majority indicated using free online resources frequently for medical education. Enrolled final year students viewed, on average, 1.24 topics per day and continued to use UpToDate frequently after graduation from medical school. Graduating class exam performance was better after introduction of UpToDate than in previous years. Conclusions: Removal of the cost barrier was sufficient to generate high uptake of a leading EBCR by senior medical students and habituate them to continued usage after graduation.